Quality of case ascertainment in cancer registries: A proposal for a virtual three-source capture-recapture technique - Suwanrungruang K. (2014)
Background: The ability and behaviour of the capture-recapture method using a virtual three-source model for evaluation of the level of completeness of case ascertainment requires exploration. Methods: Cancer cases obtained from 9 population-based cancer registries in Thailand during 2003 to 2007 were applied for capturerecapture using a model based on clinical, pathological and mortality data. These three virtual sources were derived from three actual items common to all cancer registries: the basis of diagnosis, ICD-O morphology code, and last known patient status. Poisson regression models were fit to the data to estimate parameters which were then transformed into demographic values. A linear model was used to determine the predictors and estimated percentage of completeness (EPC) in case ascertainment among the cancer registries. Results: The EPC was greater than 97% in 5 and less than 90% in 4 registries. The worst had an EPC of 70%. The percentage death certificate only (%DCO) and the interaction between %DCO and morphological verification (MV) were significantly associated with EPC. Other factors intrinsic to registries also exerted influence on the EPC. Conclusions: In addition to other standard indicators to monitor completeness of cancer registries, the present virtual three-source capture-recapture model can be routinely used to estimate the level of completeness of case ascertainment in cancer registries.